Design and Realization of Temperature and Speed Control System of Meyer Rod Coating Based on Arduino for Silver Nanowires Thin Film Applications - Junaidi, Junaidi; Irvana, Raihan; Ayu, Humairoh Ratu; Karo , Pulung Karo; Surtono, Arif; Marjunus, Roniyus; Hadi, Sutopo (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2023)
The design and implementation of an Arduino-based temperature and speed control system for Meyer rod coating have been successfully accomplished. The tool is capable of automatically regulating the temperature and speed of the plate and Meyer rod. The components utilized in manufacturing the coating tool include Arduino Uno, stepper motor, thermocouple sensor, heating plate, relay, stepper motor driver (TB6560), and thermocouple sensor supported by the MAX-6675 module. The motivation behind developing this tool stems from the inconsistency in temperature and speed during manual Meyer rod coatings, where substrate transfer to the heater is done manually. Therefore, the purpose of this tool is to make the rod's pressure and speed stable, and the substrate does not need to move. The results of this study are that the stepper motor achieved a remarkable speed accuracy of 99%, and the thermocouple sensor exhibited an accuracy of 88.43%. Further, the time required for the heater to reach 100 °C was 09.45 minutes.